The application and perspective of hyperbaric oxygen therapy in acute ischemic stroke: From the bench to a starter? - Yan, Yujia; Zhang, Xiqiang; An, Xingwei; Fan, Wanpeng; Liang, Jingbo; Luo, Bin; Ren, Hecheng; Huang, Ying (Frontiers in Neurology, 2022)
Stroke has become a significant cause of death and disability globally. Along with the transition of the world's aging population, the incidence of acute ischemic stroke is increasing year by year. Even with effective treatment modalities, patients are not guaranteed to have a good prognosis. The treatment model combining intravenous thrombolysis/ endovascular therapy and neuroprotection is gradually being recognized. After the clinical translation of pharmacologic neuroprotective agents failed, non-pharmacologic physical neuroprotective agents have rekindled hope. We performed a literature review using the NCBI PubMed database for studies that focused on the application of hyperbaric oxygen therapy in acute ischemic stroke. In this review, we present the history and mechanisms of hyperbaric oxygen therapy, focusing on the current status, outcomes, current challenges, perspective, safety and complications of the application of hyperbaric oxygen in animal experiments and human clinical trials. Hyperbaric oxygen therapy, a non-pharmacological treatment, can improve the oxygenation level at the ischemic lesions in increased dissolved oxygen and oxygen diffusion radius to achieve salvage of neurological function, giving a new meaning in acute ischemic stroke.